Christianity and global law
1 online resource.
Keywords: "This book explores both historical and contemporary Christian sources and dimensions of global law, and includes critical perspectives, comparative perspectives, and dialectics with other faiths and liberal philosophical perspectives. Leading scholars from various disciplines discuss the constituent principles of this new global legal order, historically, comparatively, and currently. Besides common principles, the project also explores how Christianity in particular can affect different concrete areas of emerging global law. The first part uses a historical-biographical approach to study a few of the major Christian architects of global law and transnational legal theory, from St. Paul to Jacques Maritain. The next part distils the deep Christian sources and dimensions of the main principles of global law, historically and today, separating out the distinct Catholic, Protestant, and Orthodox Christian contributions as appropriate. Finally, the authors address a number of pressing global issues and challenges, where a Christian-informed legal perspective can and should have deep purchase and influence. The work makes no claim that Christianity is the only historical shaper of global law, nor that it should monopolize the theory and practice of global law today. The hypothesis in this work is that Christianity, as one of the world's major religions, has deep norms and practices, ideas and institutions, prophets and procedures that can be of benefit as the world struggles to find global legal resources to confront humanity's greatest challenges"--